The Effect Of Lifestyle, Conformity, and E-Money on Online Shopping Consumptive Behavior In Generation Z In The City Of Mataram (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study was to determine the effect of lifestyle, conformity, and e-money on online shopping consumptive behavior in generation z in Mataram City. The type of research used is quantitative research. The population of this study is generation Z with the birth year 1997-2012 in Mataram City. The sample used in this study consisted of 120 people who were identified using purposive sampling technique. Data collection in this study used a questionnaire. The data in this study were analyzed using SEM-PLS analysis with the help of SmartPLS 4.0 software. Based on data analysis, the following results are obtained: (1) lifestyle has a positive and significant effect on online shopping consumptive behavior. (2) conformity has a positive and significant effect on online shopping consumptive behavior. Meanwhile, (3) E-Money has a positive but insignificant effect on the consumptive behavior of online shopping.